HDDs with Better Heat Dissipation Systems Designed for Search Engines Servers - Mohd Danial, Ibrahim; Ong, J. H.; Ahmad Adzlan Fadzli, Khairi (2012)
The usage of search engines such as Google, Yahoo and Bing for information seeking is inevitable and important for our daily lives. Google claims that users conduct over a billion searches a day, not including numerous downloads and queries. These search engines have hard disk drives (HDDs) as their core part for data storage. HDDs operating on average 7,200 rotation per minute (rpm) are the norm. However, high-end HDDs meant for fast responses and feedbacks require higher rotational speed and higher track density. These type of HDDs simultaneously need smart countermeasures for excessive heat rise; HDDs’ flow-induced vibration (FIV) such as arm vibrations and disk flutters, without increasing its power consumptions. Gigantic search engines or even cloud computing servers used in nowadays smart computing actually involve numerous HDDs to store these data and information for our convenience. By decreasing the heat generated by these vital core parts of the servers; the HDDs, the authors aim at a lesser energy consumption HDD. Out of the total energy consumed by these servers, only 40 to 45 percent are being used for operation. The remaining energy is consumed for cooling the server and database systems. In this paper, the authors propose a new actuator arm with a better window that will improve the heat dissipation of the HDDs system. The HDD’s actuator arm is designed using AutoDesk and exported to Comsol Multiphysics for numerical simulation. Each arm has a large windowed area for a better dissipation of heat generated due to air frictions. Another improvement that the authors proposed is by designing a novel S-shaped arm to promote better air flow. This will eventually lead to less heat generating HDDs meant for search engines servers of the internet.